The role of socioeconomic and environmental factors on the number of tuberculosis cases in Indonesia - Andi Kustanto (Jurnal Ekonomi Pembangunan, 2020)
The threat of TB continues to occur in the world. In 2018, 10 million people suffered from TB, and 1.5 million people die from this infectious disease. Referring to target 3 of Sustainable Development Goals (SDGs) goals 03 regarding good health and well-being, by 2030, end the epidemic of AIDS, TB, malaria, and neglected tropical diseases and combat hepatitis, water-borne diseases, and other communicable diseases. Based on data from the WHO, Indonesia ranks 3rd for TB cases globally. The estimated population suffering from TB is 845,000 cases; only 68 percent of cases were found and treated in 2018. The high number of TB cases in Indonesia could threaten the golden generation's opportunity in the next 2025 demographic bonus, where the number of productive age population is higher than the population non-productive age. This study found that population factors such as population, population density, and the number of poor people had a positive and significant effect on TB cases. In contrast, the GRDP per capita, the number of health workers, and literacy rates negatively affected the TB cases.Furthermore,environmental factors from the availability of proper sanitation and toilet facilities show a negative but insignificant effect on TB cases.